Syntactic Object Representation of Amharic Sentences by Function - Agajie, Berhanu Asaye (Center of Language and Cultural Studies [CLCS], 2020)
The aim of this study was to portray the Syntactic Object representation of Amharic sentences by function. Qualitative data were gathered from thirteen native speakers of Awgni (six females, seven males). Relevant data were also collected as of secondary sources. All the way through purposive sampling, 25 sentences were selected for descriptive analysis. The method of data analysis used was Labeling Algorithm XP, YP. This Algorism is problematic; in order to resolve XP, YP difficulty projection, Syntactic Object was modified (by raising XP) so that there was one visible verbal head. Result indicated that each sentence structures share Syntactic Object representations that include Tense Phrases (TPs), Noun Phrases (NPs), Verb Phrases (VPs), Prepositional phrases (PPs), Adverb Phrases (ADVPs), Determiner Phrase (DPs) and Adjectival Phrases (APs). Finally, the study puts forward a further research on how labeling Algorithm XP, H and X, Y works to describe the label of every Syntactic Object representations found within sentence structures in Amharic.